EFEKTIVITAS PEMBELAJARAN TAFSIR METODE BANDONGAN DI PONDOK PESANTREN AL-KAUTSAR TANJUNGPINANG - Islamiyah; Ramayanti, Desy (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study discusses the effectiveness of tafsir learning using the bandongan method at the Al-Kautsar Tanjungpinang Islamic Boarding School. This method is a classic approach in teaching yellow books that has been used for generations. This study aims to analyze the contribution of this method in improving students' understanding of tafsir science and the factors that influence its effectiveness. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews with kyai and students, and document analysis. Data analysis was carried out inductively to understand the effectiveness of the bandongan method in tafsir learning. The results of the study indicate that the bandongan method is effective in improving students' understanding of tafsir. The main factors that support the success of this method include the quality of the teacher, the interaction between the kyai and students, and the active involvement of students. In addition, this method also plays a role in building the character of students through the instillation of strong sanad-based morals and scientific values. However, there are challenges such as time constraints and lack of variation in the delivery of materials. Therefore, innovation is needed so that this method remains relevant to the needs of Islamic education in the modern era. The results of the study show that the bandongan method has proven to be effective in improving students' understanding of interpretation, but it needs to be developed to be more adaptive to current developments.